2020
DOI: 10.1029/2019gl084143
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Increases in Eastern Amazon and Cerrado Biomass Burning‐Sourced Tropospheric Ozone

Abstract: The decline in Amazonian deforestation rates and biomass burning activity (2001–2012) has been shown to reduce air pollutant emissions (e.g., aerosols) and improve regional air quality. However, in the Cerrado region (savannah grasslands in northeastern Brazil), satellite observations reveal increases in fire activity and tropospheric column nitrogen dioxide (an ozone precursor) during the burning season (August‐October, 2005–2016), which have partially offset these air quality benefits. Simulations from a 3‐D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 63 publications
(93 reference statements)
0
18
0
1
Order By: Relevance
“…Lei et al: Indirect contributions of global fires to surface ozone dry deposition. Moreover, weakened leaf-level transpiration following O 3 damage modulates meteorological parameters, such as surface air temperature and atmospheric relative humidity, leading to substantial biogeophysical feedbacks on surface O 3 (Lombardozzi et al, 2012;Sadiq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lei et al: Indirect contributions of global fires to surface ozone dry deposition. Moreover, weakened leaf-level transpiration following O 3 damage modulates meteorological parameters, such as surface air temperature and atmospheric relative humidity, leading to substantial biogeophysical feedbacks on surface O 3 (Lombardozzi et al, 2012;Sadiq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between air pollution and terrestrial ecosystems remain challenging due to limited process-based knowledge and the separate development of chemistry and vegetation models (He et al, 2020). At present, the feedbacks from O 3 -damaging vegetation on O 3 have only been examined by four papers (Sadiq et al, 2017;Zhou et al, 2018;Zhu et al, 2021). Sadiq et al (2017) implemented a parameterization of O 3 vegetation damage into a climate model and quantified online O 3 -vegetation coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). As burning in this biome increases, it may significantly alter atmospheric chemistry, as reported in recent study on the Eastern Amazon and Cerrado; Pope et al 27 found an increase in burning rates, mainly between 2005 and 2016. This significant increase in fires as a result of deforestation in the Amazon and the increase in fires in the Cerrado produces atmospheric CO 2 emissions to the troposphere and exacerbates the ozone problem, further accelerating global warming.…”
Section: Discussionmentioning
confidence: 71%
“…Measurements of surface [O3] in the U.S. are provided by Air Quality System (AQS, https://www.epa.gov/aqs), those over Europe are provided by European Monitoring and Evaluation Programme (EMEP, https://emep.int). The observed [O3] at Manaus, Tg Malim, and Welgegund sites are from earlier studies(Ahamad et al, 2014;Laban et al, 2018;Pope et al, 2020).…”
mentioning
confidence: 77%